National report : overview and recommendations - Australia. Royal Commission into Aboriginal Deaths in Custody; Johnston, Elliott (Canberra : Australian Govt. Pub. Service, 1991)
General summary of the final report of the Royal Commission; recommendations in full.
Extracted from the five-volume work also known as: Final Report of the Royal Commission into Aboriginal Deaths in Custody.
Keywords: Aboriginal Australians -- Criminal justice system; Prisoners, Aboriginal Australian -- Mortality; Prisoners, Aboriginal Australian -- Death; Prisons and race relations -- Australia; Police -- Complaints against -- Australia; Aboriginal deaths in custody; Law enforcement - Custody - Deaths in custody - Royal Commission; Australia